Business and fame: the operations of seventeenth-century Chinese garden builders. Issue 2 (3rd April 2022) - Lee, Sylvia W. S.
Abstract: Increasing numbers of scholars study seventeenth-century Chinese garden builders, such as Ji Cheng 計成 (b.1582) and Zhang Lian 張漣 (1587-c.1671). We are now better informed about their lives, design approaches, the gardens they designed, their clients, their social networks, their successors, and how they were respected in literati circles. However, these studies rarely consider the business operations of garden builders or the economic rewards they earned. Hence, studies often overlook two crucial points. First, scholarly discussions only view the garden builders as designers but fail to consider that they needed to make their livings in this trade. Second, seventeenth-century garden builders worked in a fiercely competitive environment. This paper will address those two oversights and investigate the business operations of garden builders, such as the roles of a garden builder in constructing gardens, how a garden builder received new project assignments, and the competitive business environment. This paper proposes that garden builders would promote their skill, establish their fame, and differentiate themselves within a competitive environment through initiating writing projects. This paper argues that garden builders became successful not only because they were great designers but also because they were competent communicators and promoters of their works.